2000
DOI: 10.1159/000030537
|View full text |Cite
|
Sign up to set email alerts
|

Massive Hematuria in Adults with Klippel-Trenaunay Syndrome Associated with Vascular Malformation of the Bladder

Abstract: Although hematuria has been reported in children with Klippel-Trenaunay syndrome, it is a rare presentation in the adult population. Two cases of massive hematuria in adults with Klippel-Trenaunay syndrome are reported here. A unique feature was venous malformations of the bladder which were responsible for massive recurrent bleeding in 1 patient. The clinical presentation and management are discussed. Conservative endoscopic and arteriographic control seems to be appropriate as initial management in these pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…GENET.) Pakter et al, 1988;Hockley et al, 1989;Shekarriz et al, 2000] and other locations, such as the bowel [Jafri et al, 1983], bones [Vollmar and Vogt, 1976;Ekerot et al, 1981], omentum [Komi et al, 1970], intracranial location [Suga et al, 1994], and diffuse intra-abdominal lymphatic malformations [Kondo et al, 1997]. To my knowledge, only 11 tumors have been described with KTS (Table XII).…”
Section: Klippel-trenaunay Syndromementioning
confidence: 99%
“…GENET.) Pakter et al, 1988;Hockley et al, 1989;Shekarriz et al, 2000] and other locations, such as the bowel [Jafri et al, 1983], bones [Vollmar and Vogt, 1976;Ekerot et al, 1981], omentum [Komi et al, 1970], intracranial location [Suga et al, 1994], and diffuse intra-abdominal lymphatic malformations [Kondo et al, 1997]. To my knowledge, only 11 tumors have been described with KTS (Table XII).…”
Section: Klippel-trenaunay Syndromementioning
confidence: 99%
“…Most of the hematuria of KTS can be relieved by conservative treatment. [ 14 ] The onset age of hematuria in this patient is relatively late, and only small varicose veins in the mucosa can be seen under cystoscope and flexible ureteroscope. Small hemangioma protrudes from the bladder mucosa, and no large hemangioma and thick veins can be seen, so the degree of hematuria is mild.…”
Section: Discussionmentioning
confidence: 91%
“…Endoscopic focal resection is not recommended at present, because it is difficult to estimate the scope and depth of abnormal blood vessels under the microscope, which may induce uncontrollable massive bleeding. [ 14 ] As for limitations,in this case, no arteriography was performed to distinguish patients from Parkes-Weber syndrome, and interventional therapy was not used to evaluate the treatment of malformed veins and hemangioma. On the other hand, we may be able to delay or control the progression of the disease as much as possible through gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Shekarriz et al reported two cases of hematuria which could be controlled by endoscopic and arteriographic procedures [6]. Other authors suggest fulguration and laser procedures as initial management [7,8].…”
Section: Discussionmentioning
confidence: 99%